ANALISIS PREFERENSI KONSUMEN DALAM MEMBELI DAGING BROILER DI PASAR TRADISIONAL KOTA MANADO (STUDI KASUS â€œPASAR PINASUNGKULAN KAROMBASANâ€) - Simarmata, Lasmaria; Osak, R E.M.F; Endoh, E K.M; Oroh, F N.S (ZOOTEC, 2019)
ABSTRACT ANALYSIS OF CONSUMER BUYING PREFERENCES IN BROILER MEAT AT TRADITIONAL MARKET IN MANADO CITY (CASE STUDY OF THE "PINASUNGKULAN KAROMBASAN MARKET"). The goals of this study was to analyze consumer preference and attitude on attribute variation of broilers at the traditional market in Manado. Study was conducted at the Pinasungkulan market, Karombasan Manado on February 2019. Survey method was used by deep interview supported by questionnaire. Samples were defined by accidental sampling method involving fifty respondents. The primer and secondary data were used in this study and analyzed by Chi-Square and Multi attribute Fishbein analysis. The Chi-Square analysis indicated that all attributes studied were significantly different. This was meaning that there were differences of consumers preference on broilers. On the basis of Multi attribute Fishbein analysis indicated that all broiler attribute were considered by consumers in making decision of buying broilers. Broilers were became consumer preference significantly at the Pinasungkulan Market, meaning that there was difference of consumer preference on broiler attributes. Sequences of broiler attribute from the highest consideration to the lowest consideration were meat color, skin color, meat smell, skin tenderness and meat weight. Consumer attitude on broiler meat attributed in decision of buying meat of broilers was broiler meat color. Keywords: Broiler, consumer preference